Dietary phytochemical index and psychological disorders in a large sample of Iranian adults: a population-based study - Zahra Darabi; Aazam Ahmadi Vasmehjani; Amin Salehi-Abargouei; Masoud Mirzaei; Mahdieh Hosseinzadeh (BMC, 2023)
Abstract Background Intake of plant foods and phytochemicals can decrease the odds of mental health. Aim The aim of study is to investigate the association between Dietary Phytochemical Index (DPI) with symptoms of depression, anxiety and stress in a large sample of Iranian adults. Methods In this cross-sectional study, a total of 7385 adults aged 20-50 years old were provided from the recruitment phase of Yazd Health Study, a population-based cohort research on Iranian adults. Food intakes were assessed via a validated and reliable food frequency questionnaire. Symptoms of depression, anxiety and stress were assessed using a validated Depression, Anxiety and Stress Scales questionnaire with 21-items. DPI was calculated by the percent of daily energy intake taken from phytochemical-rich foods. Results After adjustment for potential confounders, normal weight subjects in the highest tertile of DPI had lower odds of depression (OR 0.65; 95% CI 0.44-0.97) and anxiety symptoms (OR 0.65; 95% CI 0.45-0.93) compared with those in the lowest tertile. However, the apparent association was not found between depression, anxiety and stress in overweight and obese subjects. Conclusion We found a significant association between DPI and mental health in normal weight adults. Prospective studies are required to approve these conclusions.